Politeness Strategies in Selected Academic Settings: Insights from Lecturer-Student Interactions in Eastern Indonesia - Anugrawati , Nunung; Syam, Ummi Khaerati (REiLA : Journal of Research and Innovation in Language, 2024)
The study addresses a critical gap in understanding how politeness strategies are navigated within the hierarchical and culturally nuanced academic interactions of Indonesian higher education. By focusing on lecturer-student dynamics at Universitas Muhammadiyah Makassar, the research explores the types and functions of politeness strategies, providing insights into how cultural and social hierarchies shape communication behaviors. Using a qualitative descriptive approach, seven lecturers and their students were observed across multiple classroom sessions. Data collection involved video recordings and field notes, analyzed through Discourse Analysis (DA). The findings reveal that lecturers predominantly employ positive politeness strategies, such as humor, informal greetings, and in-group markers, fostering a collaborative and approachable atmosphere. Conversely, students exhibit negative politeness strategies, like formal address terms and hedging, reflecting respect for authority and a preference for maintaining hierarchical boundaries. These contrasting strategies underscore a complex interplay of reducing and respecting social distance, influenced by high-context cultural norms. The implications extend beyond academia, emphasizing the need for culturally sensitive communication practices in hierarchical institutions to foster inclusivity and mutual understanding. By bridging theoretical frameworks with real-world classroom dynamics, this study enriches the discourse on politeness and its critical role in educational settings, particularly in Eastern Indonesia contexts where power and cultural norms intersect profoundly.